Misfit and fracture load of implant-supported monolithic crowns in zirconia-reinforced lithium silicate - Rafael Soares GOMES; Caroline Mathias Carvalho de SOUZA; Edmara Tatiely Pedroso BERGAMO; Dimorvan BORDIN; Altair Antoninha DEL BEL CURY
Abstract Zirconia-reinforced lithium silicate (ZLS) is a ceramic that promises to have better mechanical properties than other materials with the same indications as well as improved adaptation and fracture strength. Objective In this study, marginal and internal misfit and fracture load with and without thermal-mechanical aging (TMA) of monolithic ZLS and lithium disilicate (LDS) crowns were evaluated. Material and methods Crowns were milled using a computer-aided design/computer-aided manufacturing system. Marginal gaps (MGs), absolute marginal discrepancy (AMD), axial gaps, and occlusal gaps were measured by X-ray microtomography (n=8). For fracture load testing, crowns were cemented in a universal abutment, and divided into four groups: ZLS without TMA, ZLS with TMA, LDS without TMA, and LDS with TMA (n=10). TMA groups were subjected to 10,000 thermal cycles (5-55°C) and 1,000,000 mechanical cycles (200 N, 3.8 Hz). All groups were subjected to compressive strength testing in a universal testing machine at a crosshead speed of 1 mm/min until failure. Student's t-test was used to examine misfit, two-way analysis of variance was used to analyze fracture load, and Pearson's correlation coefficients for misfit and fracture load were calculated (α=0.05). The materials were analyzed according to Weibull distribution, with 95% confidence intervals. Results Average MG (p<0.001) and AMD (p=0.003) values were greater in ZLS than in LDS crowns. TMA did not affect the fracture load of either material. However, fracture loads of ZLS crowns were lower than those of LDS crowns (p<0.001). Fracture load was moderately correlated with MG (r=-0.553) and AMD (r=-0.497). ZLS with TMA was least reliable, according to Weibull probability. Conclusion Within the limitations of this study, ZLS crowns had lower fracture load values and greater marginal misfit than did LDS crowns, although these values were within acceptable limits.